"Liver-on-a-Chip" Cultures of Primary Hepatocytes and Kupffer Cells for Hepatitis B Virus Infection. - Ortega-Prieto, Ana María; Skelton, J.K.; Cherry, Catherine; Briones-Orta, Marco Antonio; Hateley, Charlotte Alexandra; Dorner, M (JoVE, 2019)
Despite the exceptional infectivity of the hepatitis B virus (HBV) in vivo, where only three viral genomes can result in a chronicity of experimentally infected chimpanzees, most in vitro models require several hundreds to thousands of viral genomes per cell in order to initiate a transient infection. Additionally, static 2D cultures of primary human hepatocytes (PHH) allow only short-term studies due to their rapid dedifferentiation. Here, we describe 3D liver-on-a-chip cultures of PHH, either in monocultures or in cocultures with other nonparenchymal liver-resident cells. These offer a significant improvement to studying long-term HBV infections with physiological host cell responses. In addition to facilitating drug efficacy studies, toxicological analysis, and investigations into pathogenesis, these microfluidic culture systems enable the evaluation of curative therapies for HBV infection aimed at eliminating covalently closed, circular (ccc)DNA. This presented method describes the set-up of PHH monocultures and PHH/Kupffer cell co-cultures, their infection with purified HBV, and the analysis of host responses. This method is particularly applicable to the evaluation of long-term effects of HBV infection, treatment combinations, and pathogenesis.
Keywords: Hepatitis B - Aspectos genéticos; Virology; Hepatitis; Virus